Analisis Hukum Penggunaan Antariksa dalam Upaya Mendukung Operasi TNI AU Guna Pertahanan Negara dan Keamanan Nasional - I Gede Eka Santika; Bambang Widarto (Neolectura, 2026)
This study examines the utilization of space technology for national defense purposes in Indonesia, specifically in supporting the operations of the Indonesian Air Force (TNI AU). As global challenges grow, space has become an increasingly important strategic domain, not only for civilian purposes but also for military use. While Indonesia has regulations related to space, such as Law No. 21/2013 on Space, this study finds that the existing regulations do not specifically address the use of space for military purposes, particularly in supporting TNI AU military operations. Through library research and interviews with aerospace law experts and military practitioners, this study identifies legal gaps that need to be addressed, as well as the urgency of updating regulations to respond to the rapid development of space technology. Such updates are essential to ensure that TNI AU can optimally utilize space for surveillance, communication, and defense of Indonesia’s airspace. With clear regulatory updates, it is hoped that Indonesia can enhance its national defense capabilities and safeguard strategic interests in space